Acoustic Characteristics of Tense and Lax Vowels Across Sentence Position in Clear Speech - (:unkn) unknown (My University, 2013)
The purpose of this study was to examine the acoustic characteristics of tense and lax vowels across sentence positions in clear speech. Recordings were made of 12 participants reading monosyllabic target words at varying positions within semantically meaningful sentences. Acoustic analysis was completed to determine the effects of Style (clear vs. conversational), Tenseness (tense vs. lax), and Position (sentence-medial vs. sentence-final) on vowel duration, vowel space area, vowel space dispersion, and vowel peripheralization. The results showed speakers had longer durations and expanded vowel spaces in clear speech for both tense and lax vowels. Importantly, the amount of increase was similar for tense and lax vowels suggesting the defining properties of lax vowels (i.e., short duration and centralization) were manipulated in clear speech. A significant main effect of position for lax vowel space expansion showed greater vowel spaces for lax vowels in sentence-medial position in clear speech. Clear speech vowel adaptations appear to be dynamic with both vowel-specific and general transformations.
Keywords: Acoustic; Clear Speech